Using Mixed Reality (MR) as an Emerging Technology for Improving Higher Education: Analysis of Mental Workload - Criollo-C, Santiago; Guerrero-Arias, Andrea; Buenaño-Fernández, Diego; Jaramillo-Alcazar, íngel; Luján-Mora, Sergio (Emerging Science Journal, 2024)
This study aims to evaluate the mental workload perceived by students when using Build_3D, a mixed reality (MR) application, as an educational tool for learning PC and smartphone hardware, as well as to analyze teachers' perceptions of its impact on the teaching process. The NASA-TLX tool was applied to measure mental workload in 60 students, assessing six dimensions: mental demand, physical demand, temporal demand, perceived performance, effort, and frustration level. Additionally, qualitative observations were collected from teachers regarding the use of MR in practical learning environments. The results show that the perceived performance dimension achieved the highest score, highlighting the application's effectiveness in improving learning outcomes. Mental and temporal demands were moderate, while effort, frustration, and physical demand were low. Teachers noted that Build_3D enhances practical learning by enabling the repetition of complex tasks and fostering student motivation through immersive experiences. As a novel contribution, the study highlights the capacity of MR tools to integrate theoretical and practical concepts in an interactive environment, reducing cognitive load and promoting autonomous and personalized learning. Doi: 10.28991/ESJ-2024-SIED1-024 Full Text: PDF